Novel Insights Into the Sulfated Glucuronic Acid-Based Anti-SARS-CoV-2 Mechanism of Exopolysaccharides From Halophilic Archaeon Haloarcula hispanica - Xu, Yueqiang; Li, Yan; You, Xin; Pei, Caixia; Wang, Zhuo; Jiao, Siming; Zhao, Xin; Lin, Xuan; Lü, Yang; Jin, Cheng; Gao, George Fu; Li, Jianjun; et al. (Frontiers in Chemistry, 2022)
The pandemic caused by SARS-CoV-2 is the most widely spread disease in the 21st century. Due to the continuous emergence of variants across the world, it is necessary to expand our understanding of host-virus interactions and explore new agents against SARS-CoV-2. In this study, it was found exopolysaccharides (EPS) from halophilic archaeon Haloarcula hispanica ATCC33960 can bind to the spike protein of SARS-CoV-2 with the binding constant KD of 2.23 nM, and block the binding of spike protein to Vero E6 and bronchial epithelial BEAS-2B cells, and inhibit the pseudovirus infection. However, EPS from the gene-deletion mutant △HAH_1206 almost completely lost the antiviral activity against SARS-CoV-2. A significant reduction of glucuronic acid (GlcA) and sulfation level in EPS of △HAH_1206 was clearly observed. Our results indicated that sulfated-GlcA in EPS is possible a main structural unit in their inhibition of binding of SARS-CoV-2 to host cells, which would provide a novel antiviral mechanism and a guide for designing new agents against SARS-CoV-2.